1988
DOI: 10.1111/j.1469-8137.1988.tb00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid‐induced progression of quiescent centre cells from G1 to S phase

Abstract: S L" M M A R YQuiescent centre cells, which are known to have their cycle extended mostly in G, and to divide rarely, are stimulated to undergo DNA synthesis in root meristems of Allium cepa L. by treatment with ascorhic acid. The effect of ascorbic acid is dramatic: 21 "" of all the cells in the quiescent centre remain in the G, phase while 79",, enter S phase. From a mean value of 2204 X l()''//m'' in water-grown roots, the \olume of the quiescent centre drops to a mean value ot 167 x lO' /(m' following trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
1
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(68 citation statements)
references
References 23 publications
6
59
1
2
Order By: Relevance
“…The mechanism(s) by which AA and/or GSH influence the development of root meristems is not certain, though attention has focused on the possible roles of these compounds as redox intermediates. The absence of detectable AA in the QC led to experiments in which roots were treated with AA, which stimulated QC cells to divide, and resulted in the suggestion that the QC arises, and/or is maintained, because of a localized depletion of AA (Kerk and Feldman, 1995;Liso et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism(s) by which AA and/or GSH influence the development of root meristems is not certain, though attention has focused on the possible roles of these compounds as redox intermediates. The absence of detectable AA in the QC led to experiments in which roots were treated with AA, which stimulated QC cells to divide, and resulted in the suggestion that the QC arises, and/or is maintained, because of a localized depletion of AA (Kerk and Feldman, 1995;Liso et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…We showed that this resulted in an increased level of ascorbic acid oxidase (AAO) mRNA, protein, and enzyme activity, as well as the localized depletion of ascorbic acid (AA) within the quiescent center (QC), a group of mitotically inactive cells within the root meristem. Since AA is necessary for the G1 to S transition in the cell cycle in root tips (Liso et al, 1988), and regulation of AA is thought to be dependent on AAO, we proposed that its depletion in root tips may be responsible for the formation and maintenance of the QC (Kerk and Feldman, 1995).…”
mentioning
confidence: 99%
“…Liso et al (1988) and Innocenti et al (1990) showed that tbe root meristetns of Allium cepa L. were stimulated by growing in ascorbic acid solution and tbat tbe quiescent centre was reduced from 1000 to 100 cells within 28 h by many of its cells entering S-phase from Gl. When transferred back to water the number of noncycling cells increased in the quiescent centre region.…”
Section: Methodsmentioning
confidence: 99%